Hypermethylated CDO1 and ZNF454 in Cytological Specimens as Screening Biomarkers for Endometrial Cancer - Wang, Lei; Dong, Lanlan; Xu, Jun; Guo, Lin; Wang, Yiran; Wan, Kangkang; Jing, Wei; Zhao, Lanbo; Feng, Xue; Zhang, Kailu; Guo, Miao; Zou, Yuliang; et al. (Frontiers in Oncology, 2022)
We aimed to estimate the diagnostic value of DNA methylation levels in cytological samples of endometrial cancer (EC) and atypical hyperplasia (AH). Two hypermethylated genes, cysteine dioxygenase type 1 (CDO1) and zinc finger protein 454 (ZNF454), in EC patients were identified from the Cancer Genome Atlas database. In 103 endometrial histological specimens (the training set), the methylation levels of candidate genes were verified by quantitative methylation-specific polymerase chain reaction (qMSP). The methylation levels of another 120 cytological specimens (the testing set) were evaluated. Sensitivity, specificity, accuracy, and area under the curve (AUC) were determined, with diagnosis verified by histopathological results. CDO1 and ZNF454 verified hypermethylation in histological specimens of patients with EC and AH compared with those with benign and normal endometrium (P<0.001). In cytological specimens, hypermethylated CDO1 showed 86.36% sensitivity and 90.79% specificity with the cut-off value of 6.0 to distinguish between malignant and benign groups; ZNF454 showed 79.55% sensitivity and 93.42% specificity with the cut-off value of 7.1. When the two genes were combined, sensitivity increased to 90.91% and specificity was 86.84%. AUC reached 0.931 (95% CI: 0.885-0.976). The diagnostic accuracy with cytology had no significant difference with endometrial tissue (P=0.847 for CDO1, P=0.108 for ZNF454 and P=0.665 for their combination). Hypermethylated CDO1 and ZNF454 in endometrial cytology showed high Se, Sp and AUC to detect EC and AH. Methylation analysis of endometrial cytology are promising biomarkers for the screening of EC and AH.